The effect of prenatal methamphetamine exposure on recognition memory in adult rats - Fialová, Markéta; Šírová, Jana; Valešová, Věra; Šlamberová, Romana (Prague Medical Report, 2015)
The use of methamphetamine (MA) among pregnant women is an increasing world-wide health problem. Prenatal MA exposure may cause changes in foetus but the exact effects have remained unclear. The aim of this study is to present the effect of prenatal MA exposure on recognition memory in adult rats. Adult female Wistar rats were injected daily with D-methamphetamine HCl (MA; 5 mg/kg, s.c.) during the entire gestation period. Control females were treated with saline in the same regime. Adult male offspring was administrated acutely by MA (1 mg/kg i.p.) or saline 30 minutes before beginning of an experiment. For testing recognition memory two tasks were chosen: Novel Object Recognition Test (NORT) and Object Location Test (OLT). Our results demonstrate that prenatally MA-exposed animals were worse in NORT independently on an acute administration of MA in adulthood. Prenatally MA-exposed rats did not deteriorate in OLT, but after acute administration of MA in adulthood, there was significant worsening compared to appropriate control. Prenatally saline-exposed offspring did not deteriorate in any test even after acute administration of MA. Our data suggest that prenatal MA exposure in rats cause impairment in recognition memory in adult offspring, but not in spatial memory. In addition, acute administration of MA to controls did not deteriorate either recognition or spatial memory.
Keywords: methamfetamin; Recognition, Psychology; Animals; novorozená zvířata; Rats; Methamphetamine; Female; rozpoznávání (psychologie); Rats, Wistar; ženské pohlaví; těhotenství u zvířat; Animals, Newborn; chování zvířat; těhotenství; Memory; zpožděný efekt prenatální expozice; Male; modely nemocí na zvířatech; Prenatal Exposure Delayed Effects; Disease Models, Animal; krysa rodu Rattus; Behavior, Animal; paměť; Pregnancy, Animal; stimulanty centrálního nervového systému; zvířata; mužské pohlaví; Pregnancy; Central Nervous System Stimulants; potkani Wistar